South-North trade, intellectual property jurisdictions, and freedom to operate in agricultural research on staple crops - Binenbaum, Eran; Nottenburg, Carol; Pardey, Philip G.; Wright, Brian D.; Zambrano, Patricia (University of Chicago Press, 2003)
A biotechnology revolution is proceeding in tandem with international proliferation of intellectual property regimes and rights. Does the intellectual property impede agricultural research conducted in, or of consequence for, developing countries? This question has important spatial dimensions that link the location of production, the pattern of international trade, and the jurisdiction of intellectual property. Our main conclusion is that the current concerns about the freedom to operate in agricultural research oriented towards food crops for the developing world are exaggerated. Rights to intellectual property are confined to the jurisdictions where they are granted, and, presently, many of the intellectual property (IP) rights for biotechnologies potentially useful to developing-country agricultural producers are valid only in developed countries.